Análisis de la cadena productiva del cultivo de cáñamo (Cannabis sativa L.) en el Ecuador - Segobia Muñoz, Manuel Alberto (2023)
Hemp has the potential to be a very sustainable and environmentally friendly crop. It in turn has proven to be an excellent carbon storage and biofuel, has the ability to successfully suppress weeds and is generally considered a pesticide-free crop. Hemp and its derivatives are mainly used to produce fibers that are widely used in the textile industry to make yarns and fabrics, ropes and canvas. Other parts of the plant are used in industry to produce paper, reinforcements for building materials, insulating materials, bioenergy and much more. Hemp seeds are also valuable. They contain high quality oil that is currently used in the food, pharmaceutical, medical and cosmetic industries. The seeds are rich in protein with a balanced amino acid profile and are used in food supplements. The oilcake produced during oil extraction is a rich source of protein that is used as a feed additive for animals. This research reviews the historical and current literature on industrial hemp, focusing on the characteristics and techniques of hemp cultivation. The proecological aspect of hemp cultivation, the low soil and water requirements and the possibility of processing make us optimistic about the development of this production sector and related scientific activities.